2015
DOI: 10.1108/jap-07-2014-0026
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to elder abuse in Ethiopia

Abstract: Purpose -The purpose of this paper is to increase understanding of elder abuse in Ethiopia by considering the perspectives of abused elders. Design/methodology/approach -A phenomenological study was conducted to investigate the lived experience of 15 elders (six men, nine women) in Ethiopia who experienced domestic abuse. Data were collected using unstructured interviews and were analyzed using interpretive phenomenological analysis. The results described here focus on Ethiopian elders' perceptions of factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
1
26
0
2
Order By: Relevance
“…Older people identified that the death of their spouse, especially when the deceased spouse was active in providing emotional and material supports, makes older people experience difficulties meeting basic needs. Older people's deprivations found in this study affirm the finding that when support providers are lost, it often results in elder neglect or abuse (Chane & Adamek, 2015). The evidence in the current study also supports the ecological theory asserting that personal characteristics of older people, such as being a widow following the death of one's partner, have the potential to deprive older people of meeting essential needs (Perel‐Levin, 2008).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Older people identified that the death of their spouse, especially when the deceased spouse was active in providing emotional and material supports, makes older people experience difficulties meeting basic needs. Older people's deprivations found in this study affirm the finding that when support providers are lost, it often results in elder neglect or abuse (Chane & Adamek, 2015). The evidence in the current study also supports the ecological theory asserting that personal characteristics of older people, such as being a widow following the death of one's partner, have the potential to deprive older people of meeting essential needs (Perel‐Levin, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…Ecological perspective mainly identifies elder neglect as an issue, which culminates in the interaction between the features of older people, their relationship with others, elements of the community and macro factors, including policies and laws. As demonstrated by other studies, relevant factors such as the depleting standard of respect for elders, poor health of caregivers or older people, mutual dependency, and economic well‐being of older people and their families can contribute to elder neglect (Chane,2014; Chane & Adamek,2015).…”
Section: Introductionmentioning
confidence: 92%
“…Violence occurring within the family was discussed in 15 articles [35,39,43,44,46,48,49,55,63,66,68,69,71,76,79], with perpetrators including family members not including children [27,43,44,48,49,59,63,68,69,71] and adult children [35,39,48,66,76,79]. Studies captured instances of physical and verbal aggression by mentally ill adult children against older women [66], violence enacted by elderly with dementia against older women who were caregivers [46], and forms of neglect, financial exploitation and emotional abuse enacted by family members, including children [44].…”
Section: Descriptions and Patterns Of Types Of Violencementioning
confidence: 99%
“…Financial control spanned instances of elder abuse, family violence and IPV [43,53,62,64,76,78], and was described as co-occurring with and resulting in other forms of violence. Financial exploitation could result in emotional and/ or physical violence if older women resisted control [62,64].…”
Section: Descriptions and Patterns Of Types Of Violencementioning
confidence: 99%
“…Risk factors that may increase the potential for abuse of an older person can be identified at different levels and include: individual; poor physical and mental health of the victim, mental disorders and alcohol/substance abuse in the abuser etc., relationship; shared living situations, poor family relationships etc., community; social isolation of caregivers and older persons, and socio-cultural beliefs and practices [27][28][29][30].…”
Section: The Challenge Of Elder Abusementioning
confidence: 99%